Influence of Organizational Culture and Internal Control on Accounting Information Systems - Abdul Muti; Gatot Wahyu Nugroho; Elan Eriswanto (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study aims to determine the effect of organizational culture and internal control on accounting information systems using partial t-test and simultaneous F-test. The method used in this study is a quantitative method that uses parametric statistics. Data collection techniques in this study by conducting interviews, distributing questionnaires, documentation and literature. The population and sample in this study were 33 in the Waluran Health Center, Jampang Kulon Health Center, and Surade Health Center. The data analysis technique in this research is by testing the validity test. Reliability test, classical assumption test, multiple regression test, and hypothesis testing. The results of this study assisted by SPSS can be concluded that Organizational Culture and Internal Control have a positive and significant effect on accounting information systems